Hydrogen-dominated metal-free growth of graphitic-nitrogen doped graphene with n-type transport behaviors. (May 2020) - Yang, Jie; He, Wanzhen; Jiang, Qianqing; Chen, Zhihui; Ju, Huanxin; Xue, Xudong; Xu, Zhiping; Hu, PingAn; Yu, Gui
Abstract: Controllable nitrogen doping, an effective way to regulate the electronic property of graphene, has been achieved on metal catalyst which needs to be removed by additional processes when fabricating electronic devices, giving rise to structural damages and contaminations. Here, by using pyridine as the sole source of carbon and nitrogen, a metal-free thermal chemical vapor deposition method is demonstrated to synthesize nitrogen-doped graphene (NG) on dielectrics (SiO2 /Si, quartz, rock crystal, and sapphire). It is discovered that increasing H2 flow could promote the quality of graphene and the proportion of graphitic-N. At an optimal growth temperature of 1000 °C, we realize the controllable synthesis of graphitic-N doped graphene. Impressively, field-effect transistors directly fabricated from the N-doped graphene (∼1.1%) films on SiO2 /Si exhibit strong n -type semiconducting behaviors with electron mobilities of 110–283 cm 2  V −1  s −1 in air, rivaling heavily doped NG grown on metals. As revealed by density functional theory calculations, compared with NG with multiple types of nitrogen atoms, single graphitic-N doping leads to more prominent n- type transport behaviors, owing to the absence of p -type pyrrolic-N and pyridinic-N. Graphical abstract: Image 1 Highlights: By using pyridine as the sole precursor, N-doped graphene was directly grown on dielectrics by atmosphere pressure chemical vapor deposition. The H2 flow rate plays critical role in controlling the quality, morphology, and N atoms of N-doped graphene Controllable synthesis of high quality substitutional-N doped graphene was achieved. FET devices showed typical n- type behaviors with electron mobilities of up to 283 cm 2 V −1 s −1 in air.